Experiences of psychotherapists working with refugees in Germany: a qualitative study - Asfaw, Baye Berihun; Beiersmann, Claudia; Keck, Verena; Nikendei, Christoph; Benson-Martin, Janine; Schütt, Inken; Lohmann, Julia (BMC psychiatry, 2020)
Despite a high burden of mental health problems among refugees, there is limited knowledge about effective mental health care provision for this group. Although substantial efforts in understanding the complexity of cross-cultural psychotherapy - which in the context of this study we use to refer to therapy with client and therapist of different cultural backgrounds - have been made, there remains a dearth of research exploring barriers for effective cross-cultural psychotherapy. This study aimed at narrowing this gap in knowledge by exploring major challenges encountered by psychotherapists in cross-cultural psychotherapy and strategies which have proven useful in overcoming such challenges.
Gesehen am 19.01.2021